Differences in antimicrobial resistance of Salmonella spp. isolated from humans, animals and food products in Kazakhstan - RYCHSHANOVA, R; RUZAUSKAS, M; CHUZHEBAYEVA, G; MOCKELIUNAS, R; MAMIYEV, N; VIRGAILIS, M; SHEVCHENKO, P; SIUGZDINIENE, R; ANSKIENE, L; MENDYBAYEVA, A (Journal of the Hellenic Veterinary Medical Society, 2021)
The aims of this study were twofold: 1. to isolate Salmonella spp. from different sources in Kazakhstan, to determine their serovars and resistance profiles and 2. to evaluate similarities in antimicrobial susceptibility of Salmonella spp. isolated from humans, animals and food products. From the10 212 samples tested Salmonella spp. Were isolated in 47 cases. The predominant serovar isolated from humans and food products was S. Enteritidis. Although different animal species were tested the Salmonella spp. were isolated mainly from chickens and ducks. S. Enteritidis and S. Typhimurium were the most prevalent serovars in raw poultry meat. The most frequent resistances were those to nalidixic acid, ampicillin and tetracycline. Human isolates demonstrated lower resistance compared to animal and food isolates. The genes encoding antimicrobial resistance in human isolates in most cases were absent except for some isolates which harboured tet, sul, stre and bla TEM genes encoding resistance to the oldest antimicrobial classes. The situation in animals and food products was less beneficial as besides different genes, integrons associated with the horizontal gene transfer were detected. The findings suggest that antimicrobials in animal sector should be used more strictly, paying attention to critically important antimicrobials for humans and possible horizontal transfer of pathogens and their genetic determinants.